Efficacy of Ebselen Against Invasive Aspergillosis in a Murine Model - Sakita, Karina Mayumi; Capoci, Isis Regina Grenier; Conrado, Pollyanna Cristina Vincenzi; Rodrigues-Vendramini, Franciele Abigail Vilugron; Faria, Daniella Renata; Arita, Glaucia Sayuri; Becker, Tânia Cristina Alexandrino; Bonfim-Mendonça, Patricia de Souza; Svidzinski, Terezinha Inez Estivalet; Kioshima, Erika Seki (Frontiers in Cellular and Infection Microbiology, 2021)
Invasive aspergillosis is one of the major causes of morbidity and mortality among invasive fungal infections. The search for new antifungal drugs becomes imperative when existing drugs are not able to efficiently treat these infections. Ebselen, is an organoselenium compound, already successfully approved in clinical trials as a repositioned drug for the treatment of bipolar disorder and prevention of noise-induced hearing loss. In this study, we aimed to reposition ebselen for the treatment of invasive aspergillosis by showing ebselen effectiveness in a murine model. For this, BALB/c mice were immunosuppressed and infected systemically with Aspergillus fumigatus. Animals were divided and treated with ebselen, voriconazole, or drug-free control, for four days. The kidneys were used for CFU count and, histopathological and cytokine analysis. Ebselen was able to significantly reduce the fungal burden in the kidneys of infected mice with efficacy comparable with voriconazole treatment as both had reductions to the same extent. The absence of hyphae and intact kidney tissue structure observed in the histopathological sections analyzed from treated groups corroborate with the downregulation of IL-6 and TNF. In summary, this study brings for the first time in vivo evidence of ebselen efficacy against invasive aspergillosis. Despite these promising results, more animal studies are warranted to evaluate the potential role of ebselen as an alternative option for the management of invasive aspergillosis in humans.